A LOGICAL APPROACH TO VERIFICATION, EVALUATION AND PROCESSING OF INFORMATION DURING INVESTIGATIONAL JOURNALISM - Ganiyeva, Mehrangiz (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The article provides a comprehensive analysis of the central role of logical reasoning in verifying and evaluating information during the process of journalistic investigation. It examines the internal and external forms of fact-checking, their historical origins, and the stages of their integration into professional journalistic practice. The study demonstrates that the rapid growth of disinformation and cyber fraud on social networks poses a serious threat to society, undermines information security, and weakens public trust in the mass media. Using investigation cases from Kun.uz and the Subyektiv project, the article illustrates the practical application of fact-checking, revealing how false information is exposed and how manipulative techniques are identified. Furthermore, the article outlines the legal, ethical, and technical requirements for journalists, as well as systematic methods for verifying sources, comparing evidence, and conducting logical analysis. A structured list of guiding questions for planning an investigation — including the accuracy of evidence, transparency of sources, and the availability of conditions needed to continue the inquiry — is also proposed. In addition, the article analyzes the operational mechanisms of cybercriminal groups, methods they use to conceal financial flows, and common fraud schemes on online platforms. It offers practical recommendations for identifying these threats. In conclusion, the article emphasizes the importance of protecting information sources and strictly adhering to ethical standards at all stages of journalistic investigations, supported by concrete practical examples.